Efektivitas Program Sistem Informasi Aplikasi Guru Surabaya dalam Kenaikan Pangkat Guru di Sukolilo Surabaya - Nizar, Emirul Ibnu; Priambodo, Bayu (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
This study aims to simplify and accelerate the teacher administration process related to the submission of Promotion Through the Surabaya Teacher Application Information System (SIAGUS). The research method uses a descriptive qualitative method. This study uses the Theory of Effectiveness according to Edy Sutrisno (2007) consisting of five main indicators, including: Program Understanding, Right on Target, Right on Time, Achievement of Goals, and Real Change. This study uses primary data collection techniques and secondary data obtained from observation, interviews, and documentation. The results of the study indicate that the use of the Surabaya Teacher Application Information System (SIAGUS) is in accordance with 5 indicators, namely a good understanding of the program thanks to intensive socialization and increased digital literacy of teachers in the administration of promotions which were previously complicated. ; SIAGUS is also right on target, as evidenced by its ability to accelerate the verification of Credit Point Assessments (PAK) and become an example for other regions, as well as being a concrete solution to teacher complaints regarding inefficient manual systems. ; In terms of timeliness, SIAGUS accelerates the promotion process with a real-time status monitoring feature, although it still faces technical obstacles such as slow connections or servers, so infrastructure improvements are needed. ; The goal of SIAGUS has been achieved in simplifying and accelerating promotion administration, providing significant benefits for teachers in reducing administrative burdens and for the Education Office in increasing efficiency and transparency. ; The presence of SIAGUS also brings real positive changes, changing the burden of manual administration into an efficient digital process and freeing up teachers' time to focus on learning, making it an essential innovation that increases teacher job satisfaction. This success is supported by the commitment of the Education Office leadership, consistent training and mentoring programs, and adaptive ongoing evaluation.Keywords: Effectiveness, Teacher Promotion, Surabaya Teacher Application Information System (SIAGUS).